An Analysis of Students’ Achievement in Reading Comprehension through Higher Order Thinking Skills (HOTS) - Dumaris E. Silalahi; Herman Herman; Partohap Saut Raja Sihombing; Ade Sahbana Damanik; Lydia Purba (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research aims to find out the students’ achievement by using HOTS as learning strategy in reading comprehension at grade VIII of SMP Yayasan Perguruan Keluaraga Pematangsiantar. The aspect of students’ achievement overwhelming, remembering, understanding, applying, analyzing, evaluating, and creating. These aspects were seen in Descriptive text. The research subject belongs to students in class VIIIA and VIIIB. The data are collected using qualitative method, namely the type of basic interpretative studies in which the data obtained used questionnaires to the student in the form of a Google form. In collecting data questionnaires were shared to 65 respondents. It was used to describe the topic related to the phenomenon happen in reading comprehension through HOTS. The research findings highlight C1-C6 phase which almost of students gave positive response to each statement of criteria HOTS. The achievement in six aspects of reading comprehension used HOTS, they are remembering text with strongly agree scale 58,4%, understanding supporting sentence with strongly agree 50,2%, applying decoding process with agree scale 49,2%, analyzing main ideas with strongly agree 50,2%, evaluating inference with agree scale 51,7%, and creating new ideas with agree scale 53,3%.